2011
DOI: 10.1007/s10142-011-0228-1
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a wheat MYB gene in transgenic tobacco enhances resistance to Ralstonia solanacearum, and to drought and salt stresses

Abstract: MYB transcription factors play diverse roles in plant growth, developmental processes and stress responses. A full-length cDNA sequence of a MYB gene, namely TaPIMP1, was isolated from wheat (Triticum aestivum L.). The TaPIMP1 transcript level was significantly up-regulated by inoculation with a fungal pathogen Bipolaris sorokiniana and by drought treatment. TaPIMP1 encodes the MYB protein TaPIMP1 consisting of 323 amino acids. TaPIMP1 contains two MYB DNA binding domains (R2, R3), two putative nuclear localiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(63 citation statements)
references
References 34 publications
2
61
0
Order By: Relevance
“…Members of the MYC, MYB, and NAC TF families are also potential targets, as they are involved in controlling antagonism between hormone-mediated abiotic stress and pathogen response pathways. Research has already shown that their manipulation can confer tolerance to biotic and abiotic stresses in several species (Vannini et al, 2006;AbuQamar et al, 2009;H.X. Liu et al, 2011).…”
Section: Perspectives: Seeing Plant Stress Research In a New Lightmentioning
confidence: 99%
“…Members of the MYC, MYB, and NAC TF families are also potential targets, as they are involved in controlling antagonism between hormone-mediated abiotic stress and pathogen response pathways. Research has already shown that their manipulation can confer tolerance to biotic and abiotic stresses in several species (Vannini et al, 2006;AbuQamar et al, 2009;H.X. Liu et al, 2011).…”
Section: Perspectives: Seeing Plant Stress Research In a New Lightmentioning
confidence: 99%
“…TaMYB2A confers enhanced tolerances to multiple abiotic stresses in transgenic Arabidopsis (Mao et al, 2011). TaPIMP1 encodes a R2R3 MYB protein that enhances resistances to biotic and abiotic stresses in transgenic tobacco (Liu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Plant disease severity and disease resistance and plant defense enzyme activity changes are closely related (Qin, Sun, Zhao, Zhao, & Zhao,.2014;Liu et al, 2011). The results showed that the activities of POD, PPO and PAL in the transgenic lines increased rapidly after inoculation with P. sojae.…”
Section: Resultsmentioning
confidence: 99%